SWOT ANALYSIS OF CIRCLE MOTOCLEAN MOTORCYCLE WASHING BUSINESS BANDUNG - Aditya Affandi; Citra Savitri; Syifa Pramudita Faddila (Jurnal Ekonomi, 2022)
Along with the increasing number of vehicle users, cars and motorbikes, business opportunities continue to increase in terms of business and product sale. Currently, every side of the road can always be found at the maintenance service for both cars and motorbikes, especially vehicle washing services. This is because most of the people in big cities such as the city of Bandung, vehicle washing services, especially motorbikes, are a means for the community to wash motorbikes that are practical on the sidelines of busyness and daily routines. This study aims to describe the business management of motorcycle washing services, analyze the situation and conditions of the external and internal environment by using a SWOT analysis of the motorcycle washing service business at Circle Motoclean Bandung. The method used in this research is a qualitative method of data analysis techniques with three stages of data reduction, data presentation, and conclusions. The results show that operations at Circle Motoclean are still not effective and efficient in doing several things such as adding competent human resources, regeneration and adding additional tools, technology and facilities in the hope of increasing business income with the convenience of new customers and customers so that Circle Motoclean becomes a profitable business. keep growing